Assessment of Bioactive Compounds and Physiological Activities of Ethanolic and Aqueous Extracts from Black Rice, Black Rice Bran, and Milled Black Rice - Xiaolu Fu; Geon Oh; Ji-Hyun Im; June-Seok Lim; Min-Hye Kim; Ok-Hwan Lee (Applied Sciences)
Black rice (BR) is considered one of the healthiest foods worldwide. This study assessed the bioactive compound contents and antioxidant activities of the distilled water (DW) and 80% ethanol (EtOH) extracts of BR, black rice bran (BRB), and milled black rice (MBR). In addition, their anti-obesity, anti-obesogenic, and anti-muscle atrophy effects were comparatively evaluated. The results revealed that the 80% EtOH extract of BR contained higher contents of β-glucan, total flavonoids, and total phenolics (26.97 ± 0.70 mg gallic acid equivalents (GAE)/g and 16.58 ± 0.37 mg quercetin equivalents (QE)/g, respectively) and showed higher antioxidant activity than those of the BRB and MBR extracts. On the other hand, BRB contained the highest content of γ-oryzanol, which was 15.12 ± 0.03 mg/g. Moreover, the 80% EtOH extract of BR exhibited a stronger anti-obesogenic effect by downregulating adipogenesis-related proteins (PPAR-γ, C/EBP-α, and FAS) and upregulating lipolysis-related proteins (PGC-1α and CPT-1), while the BRB extract effectively increased myotube diameter and fusion index. Overall, these findings indicate that the 80% EtOH extracts of BR, BRB, and MBR, particularly the BR extract, have high potential as natural antioxidants and anti-obesity agents, with BRB showing promise in preventing muscle atrophy.